Building Stronger Literacy Foundations: Optimizing Phase A through Teacher Collaboration - Nila Febreiyani; Karsono Karsono; Septi Yulisetiani (AL-ISHLAH: Jurnal Pendidikan, 2025)
This study explores how teacher collaboration within the Kelompok Kerja Guru (KKG/Teacher Working Group) enhances foundational literacy in Phase A (Grades 1–2) of Indonesian elementary schools. Responding to the persistent issue of low literacy performance among early-grade students, the research investigates collaborative strategies to improve reading and writing skills within the framework of the Kurikulum Merdeka. Employing a qualitative case study design, the study involved 8 public elementary schools in the Yudistira Cluster, Selogiri Subdistrict. Participants included school principals, teachers, and the KKG coordinator, selected through purposive sampling. Data were collected over nine months via interviews, observations, and document analysis, then analyzed using the Miles and Huberman framework. Findings indicate that systematic collaboration in planning, implementation, and evaluation—supported by reading corners, enriched libraries, and a 15-minute daily reading routine—led to improved student engagement and foundational literacy outcomes. Teachers employed differentiated instructional strategies, including the Alphabet, Phonics, SAS, and Global Methods, tailored to students’ initial abilities. KKG meetings served as reflective spaces to share best practices and design interventions based on student data. The study highlights the potential of teacher-led learning communities to strengthen literacy instruction in low-resource settings. It recommends sustained institutional support and further research using longitudinal methods to assess long-term student outcomes. Ethical clearance was obtained, and informed consent was secured from all participants.